Insolvent trading and voluntary administration in Australia: economic winners and losers?. (14th December 2017) - Brotchie, James; Morrison, David
Abstract: Australian directors who incur debts while their companies are insolvent can be pursued by the corporate regulator for compensation when their companies fail. Under the Australian insolvent trading laws, directors no longer experience 'true' limited liability, and as expected, they adjust their behaviour as a result. Identifying director's rational behaviour in an insolvent trading world is difficult as there are no formal economic models of director decision‐making under Australian current corporate law. In this paper, we develop such a model primarily for private companies. We incorporate the threat of insolvent trading as well as director's tactical use of voluntary administration to avoid insolvent trading litigation. We show that neither a combination of insolvent trading or voluntary administration can simultaneously ensure creditors‐best outcomes, eliminate insolvent trading and reduce director underinvestment.